Literatur Review : Strengthening Science Numeracy Literacy to Improve Student Understanding in Science Learning - Amanda, Rara; Kesuma, Selfa Raya Hadi (CV. Rayyan Dwi Bharata, 2025)
Improving numeracy literacy in science learning is an important effort to deepen students' understanding of science concepts. Numeracy literacy not only includes the ability to count, but also involves data analysis, understanding of quantitative concepts and interpretation of numerical information. In the digital era, these skills are indispensable for developing critical thinking and data-based problem solving. This study aims to examine the effectiveness of innovative learning methods, such as problem-based learning (PBL) and interactive e-comics, in improving students' numeracy literacy and science understanding. The results showed that PBL was able to improve students' science literacy with moderate to high N-Gain categories, while interactive e-comics proved effective in facilitating the understanding of science concepts through interesting visuals. However, challenges such as limited facilities, low interest in reading, and differences in students' literacy levels are still an obstacle. Therefore, collaboration between teachers, schools, parents and the government is needed to create a supportive learning environment, provide adequate facilities and train teachers in teaching science numerically. With a holistic approach, students' numeracy literacy can be improved, preparing them for global challenges and technological advancements.